2011
DOI: 10.1111/j.1467-9671.2011.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Matching INSPIRE Quality of Service Requirements with Hybrid Clouds

Abstract: A lot of effort has been invested in Spatial Data Infrastructures (SDIs) during the last decade regarding interoperable standards for services and data. But still the scalability and performance of SDI services is reported to be crucial especially if they are accessed concurrently by a high number of users. Furthermore, laws and provisions such as the INSPIRE directive specify challenging requirements regarding the performance, availability and scalability of SDI services. This article presents a Hybrid Cloud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…INSPIRE is a large European Union project which seeks to unify spatial information under a coherent schema and which includes provision and visualisation of the data (Baranski et al 2011). The desire to make the data available and of use to society has resulted in a number of efforts towards cloud-based GIS, including a system for 3D visualisation of Greek water resources (Kallergis et al 2014).…”
Section: Alternative Cloud-based Gis Toolsmentioning
confidence: 99%
“…INSPIRE is a large European Union project which seeks to unify spatial information under a coherent schema and which includes provision and visualisation of the data (Baranski et al 2011). The desire to make the data available and of use to society has resulted in a number of efforts towards cloud-based GIS, including a system for 3D visualisation of Greek water resources (Kallergis et al 2014).…”
Section: Alternative Cloud-based Gis Toolsmentioning
confidence: 99%
“…In this context, a lot of effort has been invested, around the world, in (SDIs) during the last decade regarding interoperable standards for services and data [2]. Different SDI architectures have caused new obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…All the above literature demonstrates that significant efforts are taking place to utilise cloud computing for the geospatial domain whereas Foerster, et al [31] and Baranski et al [32] extended the use of a hybrid cloud i.e. a mixture of a private cloud for efficient utilisation of existing IT infrastructure and security reasons and a public cloud for QoS i.e.…”
Section: Soap/wsdl Binding Patterns For Wms Wcs-t Wfs-mentioning
confidence: 99%
“…al [31] demonstrated the effectiveness of a hybrid cloud (Open Nebula -private cloud and EC2 -public cloud) together with OGC a compliant 52°north based Web Processing Service. Baranski et al [32] demonstrated that INSPIRE-related challenging QoS requirements are not easy to achieve without a scalable high performance IT infrastructure, especially during peak times (many clients accessing services concurrently). They achieved promising results by using the hybrid cloud (Eucalyptusprivate cloud and Amazon EC2 -public cloud) architecture with OGC compliant 52°north based Web Processing Service.…”
Section: Soap/wsdl Binding Patterns For Wms Wcs-t Wfs-mentioning
confidence: 99%